PROVISION OF FORMAL EDUCATION TO ALMAJIRIS: THE ROLE OF LIBRARIES - Goodluck, Ifijeh I.; Juliana, James Iwu (European Scientific Journal, ESJ, 2012)
Provision of formal education to Almajiris has become a subject of national discourse in Nigeria today. This paper examines the concept and plight of the almajiris. It identifies parental influence, infrastructural decay of Qu.ranic schools, religious fanatism and poverty as causes of lack of formal education of almajiris. The study advocates that public and school libraries must begin to play relevant roles and contribute to the provision of formal education to almajiris. It outlines the roles public and school libraries must play in order to enhance almajiri education. In order to effectively play their roles, the study suggests that libraries should source for funds from external agencies rather than depend only on their parent institutions/organizations.